Population survey of small rodents on islands located inside a region of endemism for hantavirus pulmonary syndrome - Maroli, Malena; Burgos, Eliana Florencia; Piña, Carlos Ignacio; Gómez Villafañe, Isabel Elisa (Journal of mammalogy, 2022)
Ecological studies of rodent species, especially as reservoirs of zoonoses, can identify spatiotemporal conditions associated with irruptions of abundances, as well as predict areas and times with higher risk of disease transmission. The aims of this research were to describe and identify (i) the rodent community composition; (ii) their population structure and breeding season; (iii) temporal and spatial variations in their population abundance; and (iv) the environmental factors associated with these variations on islands of upper Paraná River Delta, a zone of endemism for hantavirus pulmonary syndrome (HPS) in Argentina (Entre Ríos and Santa Fe provinces). We carried out seasonal surveys over 3 years (2014–2017) with live capture traps on seven islands (natural protected areas and under livestock grazing). Three hundred seventy-seven sigmodontine rodents of seven species were captured. While the maximum richness was seven, only four species coexisted at most on an island at the same time. Although changes in reproduction were detected throughout the year, seasonality, land use, and vegetation structure did not explain changes in abundance of rodents. Rodent abundances were affected mainly by flooding-related factors and meteorological conditions (rainfall and temperatures). The recovery of rodent populations after river flooding was species-specific and heterogeneous. The abundance of Oxymycterus rufus and Akodon azarae was affected by El Niño Southern Oscillation (ENSO); A. azarae did not recover after the flood at least during the study period. After the flood, populations of Oligoryzomys flavescens, the reservoir of HPS, also declined; however, this species' populations were the first to recover its numbers, becoming dominant in the post-flood rodent community.